Innovation, markets and sustainable energy : the challenge of hydrogen and fuel cells - Stefano Pogutz; Pogutz, Stefano; Russo, Angelantonio; Migliavacca, Paolo (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2009)
Adopting a cross-sectional and international perspective, this title analyses the implications of introducing fuel cell technologies into the industrial system and explores the complexity of market development for new technological solutions.
The role of hydrogen in our energy future / Giorgio Simbolotti -- Transition towards sustainable energy systems: the case of hydrogen and fuel cells / Marcello Contestabile -- Fuel cells as disruptive innovation: the power to change markets / Paul Harborne, Chris Hendry and James Brown -- Build-up of a hydrogen infrastructure / Martin Wietschel, Philipp Seydel and Michael Ball -- Networks dynamics, innovation and fuel cell technologies: shaping a new industry / Stefano Pogutz, Angeloantonio Russo and Paolo Migliavacca -- Rate and dimensions of the technological knowledge base underlying fuel cell innovations: evidence from patent data / Ludovic Dibiaggio and Maryam Nasiriyar -- Balancing exploration and exploitation across firm boundaries: intra- and interorganizational learning in the fuel cell industry / Clodia Vurro and Angeloantonio Russo / Financing fuel cell market development: exploring the role of expectation dynamics in venture capital investment / Rolf Wustenhagen ... [et al.] -- The introduction of fuel cell technologies in the automotive industry: state of the art and perspectives / Paul Nieuwenhuis -- Early markets for fuel cells: an assessment of their contribution to a future hydrogen economy / Paolo Agnolucci -- Market coordination and network effects: the case of the European hydrogen and fuel cell technology platform / Stian Nygaard and Annika Rickne -- The American hydrogen strategy: cooperation in public policy / Clovis Zapata -- Japan's fuel cell technology: policy and progress / Yuko Harayama, Philippe Larrue and Kuniaki Honda -- Hydrogen: origins and where to go from here? / Marieke Reijalt.
Includes bibliographical references and index.
Keywords: Hydrogen as fuel; Fuel cells; Renewable energy sources -- Economic aspects; Renewable energy sources -- Technological innovations; Duurzame energie; Waterstof; Brandstofcellen; Wasserstoff; Brennstoffzelle; Erneuerbare Energien